Barriers to Physical Activity in Individuals with Spinal Cord Injury: A Western Australian Study - Roberton, T.; Bucks, R.; Skinner, T.; Allison, Garry; Dunlop, S. (Australian Academic Press Pty. Ltd., 2011)
This study examined barriers to physical activity reported individuals with spinal cord injury (SCI) and the degree to which these barriers differed across varying degrees of independence. Participants were 65 individuals recruited from the Western Australian Spinal Cord Injury database. Data on physical activity participation and perceived barriers to physical activity participation were collected using a cross-sectional survey and analysed using independent samples t-tests. We found that, regardless of level of ambulation or ability to transfer, few participants reported being physically active. While there were no significant differences in the amount of barriers reported by individuals with different levels of independence, the type of barriers reported varied across groups.